Diethylpyrocarbonate and permanganate provide evidence for an unusual DNA conformation induced by binding of the antitumour antibiotics bleomycin and phleomycin. - Fox, K R (1988)
DNA structural changes induced by bleomycin have been investigated using diethylpyrocarbonate and permanganate as probes under conditions in which the antibiotic binds to, but does not cut the DNA. Diethyl-pyrocarbonate shows an enhanced reaction with adenines in the presence of the antibiotic in the sequences GTA greater than GCA greater than GAA, on the 3' side of the drug cutting site (GPy). Permanganate ions display an enhanced reactivity at the second pyrimidine of the sequence GPyPy. The results are consistent with a model in which bleomycin distorts the structure of the base pair on the 3' side of its binding site.